A revision of the Holarctic genus Spiriverpa Irwin and Lyneborg (Diptera: Therevidae: Therevinae) - Webb, Donald W. (Zootaxa, 2005)
The genus Spiriverpa Irwin and Lyneborg is revised and includes 6 species within the Holarctic Region. Thereva bella nigrimana Kröber is synonymized under Spiriverpa bella (Kröber), Thereva candidata Loew is synonymized under Spiriverpa senex (Walker), Thereva cockerelli Cole is synonymized under Spiriverpa albiceps (Loew), and Spiriverpa sublunulata Zaitzev is synonymized under Spiriverpa argentata (Matsumura). Each species is redescribed with illustrations of their genitalia, a key to their identification, a map of their distribution, and a phylogenetic hypothesis of their relationships within Spiriverpa.